1986
DOI: 10.1161/01.str.17.6.1284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allopurinol on ischemia and reperfusion-induced cerebral injury in spontaneously hypertensive rats.

Abstract: In spontaneously hypertensive rats, we studied the participation of xanthine oxidase-linked free radical in ischemia and reperfusion-induced cerebral injury, using allopurinol, a xanthine oxidase inhibitor. The loss of righting reflex was noted in some animals after a 4 hour occlusion of bilateral common carotid arteries and 19 of 25 animals died within 72 hours after reperfusion. One hour after reperfusion, the cerebral water content increased significantly, with an increase in sodium content and a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

1986
1986
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(32 citation statements)
references
References 24 publications
(13 reference statements)
1
27
0
4
Order By: Relevance
“…This implies that some mechanism to generate oxygen radicals still works and aggravates ischemic damage in permanent ischemia caused by occluding cerebral arteries. Allopurinol reduced infarct volume of cortical tissue more effectively than caudate tissue (11), suggesting that a collateral blood supply existed in the cortical area where the branches of MCA have extensive anastomoses with distal branches of the anterior and posterior cerebral arteries (12). During the period of ischemia, the depletion of tissue ATP due to the restriction of its production results in an elevated concentration of AMP.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that some mechanism to generate oxygen radicals still works and aggravates ischemic damage in permanent ischemia caused by occluding cerebral arteries. Allopurinol reduced infarct volume of cortical tissue more effectively than caudate tissue (11), suggesting that a collateral blood supply existed in the cortical area where the branches of MCA have extensive anastomoses with distal branches of the anterior and posterior cerebral arteries (12). During the period of ischemia, the depletion of tissue ATP due to the restriction of its production results in an elevated concentration of AMP.…”
Section: Discussionmentioning
confidence: 99%
“…This adverse reaction to chronic allopurinol administration is in sharp contrast to the benefits of this drug in other organ systems (e.g., it attenuates ischemia and reperfusion-induced cerebral injury in this hypertensive strain). 20 We used the endogenous creatinine clearance as an index of the glomerular filtration rate and kidney function. There are inherent inaccuracies with this method due to incomplete bladder emptying and a variable contribution of tubular secretion to creatinine excretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it takes longer for the hypoxanthine-xanthine oxidase system and activated neutrophils to generate superoxide radicals, sl-36 Therefore, excessive generation of superoxide radicals on the third and fifth days after reperfusion in the present study may result from the hypoxanthine-xanthine oxidase system and from activated neutrophils. Ito et al 37 reported amelioration of ischaemia/reperfusion cerebral damage by administering a xanthine oxidase inhibitor. Shiga et al ss reported that pretreatment of monoclonal antibody ofneutrophils inhibited the brain oedema on the day following a transient ischaemia, probably due to exhaustion of circulatory neutrophils.…”
Section: Figure Continued On Page 230mentioning
confidence: 99%